População de plantas e componentes de produção de milho pipoca - Queiroz, Dyane Coelho (2011)
The aim of this study was to evaluate the effect of plant population on yield components of two hybrids of popcorn, in periods of "off-season" 2010 and "Yield" summer of 2010/2011. The experiments took place at the Experimental Farm of Iguatemi district of Maringa, Northwest of Parana, in area of occurrence of Red Nitosol, argyle texture. The experimental design was randomized complete block with treatments with four replications in a factorial 5 x 2, resulting from the combination of five plant populations (40,000; 55,000; 70,000; 85,000 and 100,000 plants ha-1) and two commercial hybrids popcorn (IAC-112 and IAC-125), the plots were spaced 0.9 m between rows. The experimental data were subjected to variance analysis with their individual developments. The effects of plant populations were studied by means of polynomial regression and the effects of the hybrids were compared by F test using the statistical program Sisvar. During the off season in 2010, observed an effect of population density on the characteristics of leaves, stem diameter and leaf area index, as well as for yield components of spike length, capacity expansion and productivity grains. As regards the cultivation of "Summer" 2010/2011, the densities influenced significantly on the characteristics, stem diameter and leaf area index, and there are still effects of increased plant density on components production, average number of kernels per row, expandability, and grain yield.